1982
DOI: 10.1002/1097-4679(198204)38:2<439::aid-jclp2270380240>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a provocation on aggression for three types of alcohol users

Abstract: Investigated the effects of a provocation on aggression for three types of alcohol users. The Alcohol Use Inventory was used to select 30 light‐moderate and 30 moderate drinkers. Thirty abstainers were selected as a control group. Half of each group was assigned randomly to one of two treatments, a provocation or a no‐provocation. After treatment, each S completed the Adjective Rating Form (ARF) verbal aggression scales and the Multiple Affect Adjective Checklist (MAACL). The results of this study indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Alcoholics are more aggressive, hostile and troubled ones. Similar results have also been reported by (Baldwin and Randolph 1982, Rajendran and Cherian 1992, Michel 2003. Further non-alcoholic individuals are higher on internal locus of control and same time give importance to powerful others.…”
Section: Discriminant Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Alcoholics are more aggressive, hostile and troubled ones. Similar results have also been reported by (Baldwin and Randolph 1982, Rajendran and Cherian 1992, Michel 2003. Further non-alcoholic individuals are higher on internal locus of control and same time give importance to powerful others.…”
Section: Discriminant Analysissupporting
confidence: 90%
“…Many studies found positive relationship between alcoholism and hostile & aggressive behavior (Baldwin & Randolph 1982, Rajendran and Cherian 1992, Michel et al 2003, Schumacher et al 2008. Abelsohn and Spuy (1978) reported that significant differences were found in hostility on different stages of ages in alcoholics.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the presence or absence of mental stress may have contributed to the radically different result. In general, the presence of a stressor increases the degree of aggression (23,24). Actually, hostility (the Multiple Affect Adjective Checklist) and aggression (the Adjective Rating Form) scales of nondrinkers were higher than those of moderate drinkers when subjects were not provoked, whereas, after provocation, both scales increased in the two groups, and those of moderate drinkers became higher than for nondrinkers (24).…”
Section: Discussionmentioning
confidence: 96%
“…In general, the presence of a stressor increases the degree of aggression (23,24). Actually, hostility (the Multiple Affect Adjective Checklist) and aggression (the Adjective Rating Form) scales of nondrinkers were higher than those of moderate drinkers when subjects were not provoked, whereas, after provocation, both scales increased in the two groups, and those of moderate drinkers became higher than for nondrinkers (24). Thus, it is possible that the results obtained from the psychological testing methods without stressor as performed in the present study were different from the previous results (12).…”
Section: Discussionmentioning
confidence: 99%